THE IMPORTANCE OF ANTIBIOTICS IN A VARIOUS UNIQUE METASTASIS ALONG WITH CYTOTOXIC THERAPY AT TERTIARY CARE HOSPITAL: A PROSPECTIVE COHORT STUDY - KIRAN, G. SAI; KUMAR, N. DOONDI PHANI (International Journal of Current Pharmaceutical Research, 2020)
Objective: Rare cancers are creating a massive challenge to the world. It has associated with genetic mutations or socio-environmental factors, which includes genes, smoking, alcohol, ionizing radiation exposure, organic-inorganic chemicals, air and water pollution, viruses, and bacteria. When 15 cases per 1,00,000 people per year, we can consider it as a rare case as per the National Cancer Institute This study aim is the importance of antibiotics in various unique metastasis along with cytotoxic therapy at tertiary care hospital. Methods: The inclusion criteria of our study include a person who is suffering from rare metastasis at an early stage. We excluded the data that are those who are suffering from the typical type of cancers, multiple co-morbid conditions. This study was carried out the Prospective Cohort Study conducted between June 2018 to March 2020. Results: Number of 20 rare cancers we consider for final analysis, the overall antibiotics use in this study 18 antibiotics they prescribed in overall cases, prescribed cytotoxic drugs are 23. the chi-square test value is P=0.001, the confidence interval(CI) is 95%, the likelihood ratio is 54.4, odd’s ratio is 2.0(CI 95%, P=0.711), Male patients more than the female patients. Conclusion: Cancer is a complex disorder, which is occurred through gene proliferation and socio-environmental factors. Rare metastasis is challenging to physicians and patients, however as per our observation, cytotoxic therapy with antibiotics can reduce the risk of rare metastasis and as well improved therapeutic adhesion, and we need clear supporting evidence on it through clinical trials.